Phase III/IV, Randomized, Fifty‐Two–Week Study of the Efficacy and Safety of Belimumab in Patients of Black African Ancestry With Systemic Lupus Erythematosus. Issue 1 (9th December 2021) - Ginzler, Ellen; Guedes Barbosa, Luiz Sergio; D'Cruz, David; Furie, Richard; Maksimowicz‐McKinnon, Kathleen; Oates, James; Santiago, Mittermayer Barreto; Saxena, Amit; Sheikh, Saira; Bass, Damon L.; Burriss, Susan W.; Gilbride, Jennifer A.; et al.
Abstract : Objective: Enrollment of patients of Black African ancestry with systemic lupus erythematosus (SLE) in phase II and phase III of the belimumab trials was not reflective of the racial distribution observed in the lupus population. This study was undertaken to assess the efficacy and safety of intravenous (IV) belimumab plus standard therapy in patients of self‐identified Black race. Methods: EMBRACE (GSK Study BEL115471; ClinicalTrials.gov identifier: NCT01632241) was a 52‐week multicenter, double‐blind, placebo‐controlled trial in adults of self‐identified Black race with active SLE who received monthly belimumab 10 mg/kg IV, or placebo, plus standard therapy. The optional 26‐week open‐label extension phase included patients who completed the double‐blind phase. The primary end point of the study was SLE Responder Index (SRI) response rate at week 52 with modified proteinuria scoring adapted from the SLE Disease Activity Index 2000 (SLEDAI‐2K) (SRI–SLEDAI‐2K). Key secondary end points included SRI response rate at week 52, time to first severe SLE flare, and reductions in prednisone dose. Results: The modified intent‐to‐treat population comprised 448 patients, of whom 96.9% were women and the mean ± SD age was 38.8 ± 11.42 years. The primary end point (improvement in the SRI–SLEDAI‐2K response rate at week 52) was not achieved (belimumab 48.7%, placebo 41.6%; odds ratio 1.40 [95% confidence interval 0.93, 2.11], P = 0.1068); however, numerical improvements favoring belimumab were observed, in which the SRI–SLEDAI‐2K response rates were higher in those who received belimumab compared with those who received placebo, especially in patients with SLE who had high disease activity or renal manifestations at baseline. The safety profile of belimumab was generally consistent with that observed in previous SLE trials. Adverse events were the primary reasons for double‐blind phase withdrawals (belimumab 5.4%, placebo 6.7%). Conclusion: The primary end point of this study was not achieved, but improvement with belimumab versus placebo was observed, suggesting that belimumab remains a suitable treatment option for SLE management in patients of Black African ancestry.